The Effect of Labour-Demand Shocks on Women’s Participation in the Labor Force: Evidence from Palestine - Fallah, Belal; Bergolo, Marcelo; Saadeh, Iman; Abu Hashhash, Arwa; Hattawy, Hashhash (Journal of Development Studies, 2020)
Two interesting facts emerge from the Palestinian labour market. Educational attainment for women swiftly expanded during the 1999–2011 period, but the labour force participation rate for educated women stagnated––disproportionately so for young educated women. We investigate whether changes in labour demand has contributed to women’s sluggish labour force participation. Our empirical analysis used quarterly labour-force data published by Palestine Central Bureau of Statistics between 2005 and 2011. To explore the causal effect of labour demand shocks, we use Bartik instrumental variable approach. Our analysis provides evidence that changes in the labour demand for educated women, rather than improvement in overall demand, affect their labour force participation. This research has important policy implications regarding the economic empowerment of educated women in Palestine suggesting that improvement in overall demand may not benefit educated women and that boosting demand for this specific cohort is what matters.
Keywords: labor force participation, demand shocks, Palestine